2015
DOI: 10.1093/heapro/dav071
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening sense of coherence: opportunities for theory building in health promotion: Fig. 1:

Abstract: Sense of coherence (SOC) reflects a coping capacity of people to deal with everyday life stressors and consists of three elements: comprehensibility, manageability and meaningfulness. SOC is often considered to be a stable entity that is developed in young adulthood and stabilizes around the age of 30. Recent studies have questioned this stability of SOC and some studies report on interventions that have been successful in strengthening SOC in adult populations. Currently, however, there is no clear understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 46 publications
4
138
0
9
Order By: Relevance
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 98%
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 98%
“…In addition, researchers have begun to study how SOC develops in childhood and early adulthood (García-Moya, Moreno, & Jiménez-Iglesias, 2013;Marsh, Clinkinbeard, Thomas, & Evans, 2007). However, further research is necessary to examine the factors that contribute to the development of SOC, the role of various developmental contexts in building up SOC (García-Moya et al, 2013) and the possibilities for strengthening SOC explicitly, for example in sport-for-development settings (Super, Wagemakers, Picavet, Verkooijen, & Koelen, 2015). As sport is often seen as a promising setting for positive youth development, taking a salutogenic approach we aim to complement the current literature in the field by investigating how community sports coaches create optimal social conditions for life skill development and transferability.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This in turn, may empower individuals to identify resources to develop more realistic goals and priorities and interpret their efforts as worthy and meaningful in mastering difficult situations. [38]…”
Section: Implications For Nursing Education and Practicementioning
confidence: 99%